Periodontal Ligament Cells Are Involved in the Formation of Intracanal Cementum-Like Tissue After Regenerative Endodontic Procedures: A Mouse in situ Model - Komada, Tomoaki; Mitomo, Keisuke; Ikarashi, Takatoshi; Shimono, Masaki; Jung, Han-Sung; Muramatsu, Takashi (Frontiers in Dental Medicine, 2022)
Regenerative endodontic cell-homing procedures are performed on injured immature teeth diagnosed with pulp necrosis and apical periodontitis. The representative histological finding after the procedures is cementum-like tissues filling in the root canal. However, detailed healing process remains unknown. We investigated histological healing process after the procedures using mouse in situ model. Regenerative endodontic procedures were experimentally performed on non-infected maxillary first molars of 6-week-old male C57BL/6 mice, after which, healing process was investigated histologically and immunohistochemically. Immediately after regenerative endodontic cell-homing procedures, blood clot was seen in the root canal, and disappeared over time. At day 7, the blood clot was replaced by granulation tissue. From day 14 onward, cementum-like tissues were filled in the root canal, while the fibrous tissue was reduced. Immunohistochemically, positive reaction for periostin were seen at the fibrous tissue in the root canal, apex and periodontal ligament cells. On the other hand, nestin positive reaction was not detected in the root canal. CD31-positive cells with a luminal structure were also observed in the fibrous tissue around the apex and around newly formed cementum-like tissues in the root canal. In this study, we have established mouse in situ model of regenerative endodontic procedure. The results of this study suggest that periodontal ligament cells and vascular endothelial cells definitely ingrow into the root canal from the apex and replace blood clot, and participate in the formation of cementum-like tissue with angiogenesis during the healing process of regenerative endodontic procedures.